Case report: The first case of Achromobacter xylosoxidans-related tunnel infection in a patient receiving peritoneal dialysis. Issue 16 (April 2017) - Tsai, Jun-Li; Tsai, Shang-Feng
Abstract: Rationale: Achromobacter xylosoxidans infection is mostly reported in immunocompromised patients. Until now, it is still rarely reported in patients undergoing peritoneal dialysis. Patient concerns: This is the 1st case of A xylosoxidans infection due to tunnel infection of a Tenckhoff catheter. Diagnosis: The diagnosis was confirmed by the report of culture. Interventions: Risk factors for this infection in peritoneal dialysis include uremia with an immunocompromised state, contamination due to inexperienced skills, and aqueous environment of the dialysate. Outcome: We believe that finding the source of A xylosoxidans contamination is the most important aspect of the overall treatment of the infection. Lessons: Environmental investigation of suspected source contamination is warranted in those with A xylosoxidans infection. Once the diagnosis is made, removal of the Tenckhoff catheter should not be delayed.